Community - Base Climate Crisis Adaptation and Engaging - Takama , Dr. Takeshi (Faculty of Public Health Mulawarman University, Indonesia, 2025)
This study examines the role of community-based adaptation in building resilience to climate change impacts. By analyzing case studies of communities implementing adaptation strategies, this research aims to identify the factors that contribute to the success of these initiatives and the challenges that hinder progress. The findings will inform the development of more effective community-based adaptation programs. This study investigates the extent to which communities are involved in decision-making processes related to climate change adaptation. By conducting surveys and interviews with community members and local government officials, this research aims to identify the barriers and facilitators to community participation and the implications for the effectiveness of adaptation measures. This study explores the role of local knowledge in informing community-based adaptation strategies. By conducting ethnographic research, this research aims to document the traditional knowledge and practices that communities use to cope with climate variability and change. The findings will contribute to the development of more culturally appropriate and sustainable adaptation solutions.